Cultural (re)translation: the case of Yohanan Simon. (2nd January 2020) - Weissbrod, Rachel; Kohn, Ayelet
ABSTRACT: This paper applies the concept of retranslation within the context of cultural translation. The revised conceptualisation of retranslation is used as a point of departure for examining the representations of Yohanan (Hans) Simon's evolving biography. Simon, an Israeli artist, translated and retranslated himself, metaphorically, both as an individual and an artist, throughout his life. By combining cultural translation with self-translation, which produces the metaphor 'cultural self-translation, ' we demonstrate how 'translation' turns into 'retranslation' when the process is repeated. In continuation of previous research on cultural translation, we show how the broad concept can be used to address issues such as migration and cultural hybridity, with an emphasis on the obvious conflicts that the artist experienced as a translated and retranslated man. Thus, we see how the biographical landmarks of Simon's life are reflected in changes of artistic style and genres, which at the same time mirror his inner conflicts and ideological transformations. To demonstrate the experience of living within the framework of ever-changing geographical and ideological borders, we used Bhabha's concept of the 'third space' as the virtual site where opposing values clash and interact, and the act of retranslating is continuously being performed and experienced.